Learning Devices Development of Learning Devices Mathematics Based on Spiritual Values for State Elementary School Students in Sumenep Regency - Ike Yuli Mestika Dewi; Fajar Budiyono; Syaiful Bahri (Universitas Muhammadiyah Enrekang, 2023)
The development of this learning tool is an effort to strengthen the intelligence of students in all aspects, especially the spiritual aspect. The development of mathematics learning is one part of the effort to form spiritual intelligence among students which in turn can become the prime generation in today's technological civilization. Mathematics is not only taught as arithmetic, but also becomes a very important religious knowledge for students in shaping their character. This research is a research on the development of theological mathematics learning tools, which describe validity (learning tools), practicality (learning implementation), and effectiveness (student activities, student responses, completeness of student learning outcomes, and obstacles encountered during the learning process). This research was carried out in several stages. First, the stage of developing integrated learning tools which is carried out by adopting the 4-D learning development model, including Define, Design, Develop, and Dissimilate. Second, the research stage is on learning tools at SDN in Sumenep district. The results of the study describe the learning tools used in this study. First, the validity of the theological mathematics learning tools, RPP, BAS, LKS and LP are considered valid and feasible to use. Second, the practicality of learning tools is taken from observational data on the implementation of learning in each meeting. Third, the effectiveness of the developed learning tools can be seen from the data of student activities, student responses, student learning outcomes tests, both student activities, student responses, student learning outcomes can be categorized as good.